Dyssegmental dysplasia, Silverman‐Handmaker type: prenatal ultrasound findings and molecular analysis. (4th August 2013) - Ladhani, Noor Niyar N.; Chitayat, David; Nezarati, Marjan M.; Laureane, Mittaz Crettol; Keating, Sarah; Silver, Rachel J.; Unger, Sheila; Velsher, Lea; Sirkin, Wilma; Toi, Ants; Glanc, Phyllis
ABSTRACT: Objectives: The objective of this study is to describe the prenatal sonographic features and the results of DNA analysis on three fetuses with dyssegmental dysplasia, Silverman‐Handmaker type (DD‐SH). Methods: A retrospective review of three fetuses with confirmed DD‐SH was conducted. The fetal ultrasound findings, the radiological characteristics, and the results of the mutation analysis of the heparan sulphate perlecan gene 2 ( HSPG2 ) were reviewed. Results: There were three cases in two families with DD‐SH diagnosed prenatally. The main prenatal ultrasound and the radiological features of DD‐SH were severe limb shortening and vertebral segmentation and fusion defects (anisospondyly). The DNA analysis of the HSPG2 gene showed that the two affected fetuses in a nonconsanguineous family had a compound heterozygote for the c.646G > T transversion in exon 7 and a c.5788C > T transition in exon 46. The fetus born to the consanguineous couple had a homozygous mutation c.1356‐27_1507 + 59del. Conclusion: DD‐SH can be diagnosed prenatally using fetal ultrasound as early as 13 weeks. Xrays and DNA analysis of the HSPG2 gene are important for the confirmation of the diagnosis and for the preimplantation and prenatal diagnosis in pregnancies at risk. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The DD‐SH is a rare skeletal dysplasia. Most cases in the literature describe the diagnosis in the second or third trimesters or in the immediate postnatal period. What does this study add? This series describes the first reported cases of DD‐SH diagnosed in the first trimester and one of the few molecularly confirmed cases in the literature.